MD Simulations on a Well-Built Docking Model Reveal Fine Mechanical Stability and Force-Dependent Dissociation of Mac-1/GPIbα Complex - Jiang, Xiaoyan; Sun, Xiaoxi; Lin, Jiangguo; Ling, Yingchen; Fang, Ying; Wu, Jianhua (Frontiers in Molecular Biosciences, 2021)
Interaction of leukocyte integrin macrophage-1 antigen (Mac-1) to platelet glycoprotein Ibα (GPIbα) is critical for platelet-leukocyte crosstalk in hemostasis and inflammatory responses to vessel injuries under hemodynamic environments. The mechano-regulation and its molecular basis for binding of Mac-1 to GPIbα remain unclear, mainly coming from the lack of crystal structure of the Mac-1/GPIbα complex. We herein built a Mac-1/GPIbα complex model through a novel computer strategy, which included a flexible molecular docking and a system equilibrium followed by a “force-ramp + snapback” molecular dynamics (MD) simulation. With this model, a series of “ramp-clamp” steered molecular dynamics (SMD) simulations were performed to examine the GPIbα-Mac-1 interaction under various loads. The results demonstrated that, the complex was mechano-stable for both the high rupture force ( > 250 pN) at pulling velocity of 3 Å/ns and the conformational conservation under various constant tensile forces (≤75 pN); a catch-slip bond transition was predicted through the dissociation probability, examined with single molecular AFM measurements, reflected by the interaction energy and the interface H-bond number, and related to the force-induced allostery of the complex; and, besides the mutation-identified residues D222 and R218, the residues were also dominant in the binding of Mac-1 to GPIbα. This study recommended a valid computer strategy for building a likely wild-type docking model of a complex, provided a novel insight to the mechanical regulation mechanism and its molecular basis for the interaction of Mac-1 with GPIbα, and would be helpful for understanding the platelet-leukocyte interaction in hemostasis and inflammatory responses under mechano-microenvironments.